Integration of GPS and GIS in Mapping of Secondary Schools in Akure South Local Government Area of Ondo State Nigeria - H. Tata; E.P. Ojo (Journal of Applied Sciences and Environmental Management)
The study aims at integrating GPS and GIS in the Mapping of secondary schools in Akure South Local Government Area of Ondo State with a view to identify, map, and create a database for both private and government secondary schools within the study area. A total number of 56 schools were identified. Garmin Map 76CSX hand-held GPS was used in acquiring their positions (coordinate in Eastings and Northings) within the study area while the attribute data was obtained from the ministry of education. The satellite image of the study area was downloaded from Google Earth website. ArcGIS 10.1 was used for the production of the digital map while Microsoft Access 2007 was used in generating the database. In performing the query, the query builder in ArcView was used. The result of the database reveals that the number of secondary schools owned by the government and private individuals are 26 and 30 respectively, representing 45% and 54% respectively of the total secondary schools within the study area. The created database reveals that some schools have complete facilities with specific laboratories for each of the science subjects while others have incomplete equipment or lack specific laboratory facilities for practical subjects. Furthermore, the study reveals that there are more private schools than government owned secondary schools within the study area.